2018
DOI: 10.1016/j.jacc.2017.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Lipids, Lipoproteins, and Metabolites and Risk of Myocardial Infarction and Stroke

Abstract: BackgroundBlood lipids are established risk factors for myocardial infarction (MI), but uncertainty persists about the relevance of lipids, lipoprotein particles, and circulating metabolites for MI and stroke subtypes.ObjectivesThis study sought to investigate the associations of plasma metabolic markers with risks of incident MI, ischemic stroke (IS), and intracerebral hemorrhage (ICH).MethodsIn a nested case-control study (912 MI, 1,146 IS, and 1,138 ICH cases, and 1,466 common control subjects) 30 to 79 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

45
366
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 367 publications
(413 citation statements)
references
References 33 publications
45
366
2
Order By: Relevance
“…Future MR studies are needed to investigate this hypothesis. Our comprehensive examination of the associations of alcohol with lipid particles and lipid constituents replicated a recent metabolomic study 7 , and revealed that alcohol may increase large HDL-C particle size, total cholesterol concentration and apolipoprotein A1, which each are associated with reduced MI risk 15 ; however, when considering coincident increases in MI increasing constituents such as small and medium LDL-C and large LDL-C particle size 15 , and, as mentioned above, the RCTs and MR studies failing to find increased HDL-C and reduced CVD risk 8,[34][35][36] , further suggests any hypothetical cardioprotective mechanism derived from HDL-C metabolism changes may be further reduced when compared to assessments failing to consider these heterogenous associations. It is possible that alcohol consumption may reduce CHD risk through its modulation of HDL-C phospholipid content, which impacts reverse cholesterol transport 47 -a pathways inversely associated with prevalent CHD, even after controlling for HDL-C levels 48 -and has been shown to be reduced among CHD patients 47 .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Future MR studies are needed to investigate this hypothesis. Our comprehensive examination of the associations of alcohol with lipid particles and lipid constituents replicated a recent metabolomic study 7 , and revealed that alcohol may increase large HDL-C particle size, total cholesterol concentration and apolipoprotein A1, which each are associated with reduced MI risk 15 ; however, when considering coincident increases in MI increasing constituents such as small and medium LDL-C and large LDL-C particle size 15 , and, as mentioned above, the RCTs and MR studies failing to find increased HDL-C and reduced CVD risk 8,[34][35][36] , further suggests any hypothetical cardioprotective mechanism derived from HDL-C metabolism changes may be further reduced when compared to assessments failing to consider these heterogenous associations. It is possible that alcohol consumption may reduce CHD risk through its modulation of HDL-C phospholipid content, which impacts reverse cholesterol transport 47 -a pathways inversely associated with prevalent CHD, even after controlling for HDL-C levels 48 -and has been shown to be reduced among CHD patients 47 .…”
Section: Discussionsupporting
confidence: 73%
“…Meta-analyses and short-term trials suggest alcohol consumption is associated with CVD risk factors including increased high-density lipoprotein-cholesterol (HDL-C) 13 ; however, the association with low-density lipoprotein cholesterol (LDL-C) and triglycerides (TRG) are less clear 14 . Variation in size, density, concentrations and composition of circulating lipids, which traditional measures are unable to distinguish, are thought to have contrasting effects to CVD risk 15 . Metabolomics provides a detailed view of systemic metabolism, and the physiological effect of alcohol consumption extends across multiple metabolic pathways 7 and has been associated with molecular dysregulation conferring both reduced and increased CVD risk 7 .…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been shown that the concentrations of small VLDL, IDL and all classes of LDL were related to carotid IMT, while large and medium size HDL were inversely related to IMT in this artery (Wurtz et al ., ). This lipoprotein profile is also seen in subjects developing a myocardial infarction or stroke in the future (Holmes et al ., ). This lipoprotein pattern is also found to be related to IMT in the carotid artery in the present study, as well as to IMT in the femoral artery, although the confidence intervals were much larger in the femoral artery.…”
Section: Discussionmentioning
confidence: 97%
“…HDL cholesterol and apoA-I are among the serum lipoprotein measures showing strongest inverse associations with cardiovascular disease in epidemiological studies. 44,45 However, large phase III cardiovascular outcome RCTs using HDL cholesterol increasing therapies have failed to identify that the risk of CAD is proportionate to the amount by which HDL cholesterol is increased, 1, 2 and, consistently, studies of human genetics find that the association of HDL cholesterol with CAD is not causal. 5,6 In the REVEAL trial of the cholesteryl ester transfer protein (CETP) inhibitor, anacetrapib, although treatment with anacetrapib did increase HDL cholesterol, the cardiovascular benefit was proportionate to the degree of apoB lowering, rather than to the effect on HDL cholesterol.…”
Section: Discussionmentioning
confidence: 99%